Contemporary social theory an introduction - Elliott, Anthony 1964- (Routledge, an imprint of the Taylor & Francis Group, 2022)
"Now in its third edition, Anthony Elliott's comprehensive, stylish and accessible introduction continues to be the indispensable guide to social theory. Fully revised and updated, the book examines the major theoretical traditions from the Frankfurt School to posthumanism, and from feminism and post-structuralism to globalization theory and beyond. Classical debates in social theory are given careful appraisal, as are the major contemporary theorists - including Jurgen Habermas, Judith Butler, Anthony Giddens, Pierre Bourdieu, Julia Kristeva, Slavoj Zizek, Manuel Castells, Ulrich Beck, Zygmunt Bauman, Shoshana Zuboff and Bernard Stiegler. This edition includes a new chapter on the digital revolution, with consideration of how digital technologies in general and artificial intelligence in particular are resahaping societies. Like its predecessors, the third edition of Contemporary Social Theory combines stylish exposition with reflective social critique and original insights. This volume will prove a superb textbook with which to navigate the twists and turns of contemporary social theory as taught in the disciplines of sociology, politics, cultural and media studies and many more"--Provided by publisher.